2021
DOI: 10.1097/jsm.0000000000000987
|View full text |Cite
|
Sign up to set email alerts
|

Midseason Screening for Groin Pain, Severity, and Disability in 101 Elite American Youth Soccer Players: A Cross-Sectional Study

Abstract: Objective:To (1) systematically screen for groin pain and type in young elite soccer players and (2) assess whether hip and groin-related severity and disability differed between players with different levels of groin pain and tenderness.Design:Cross-sectional observational.Setting:Elite American soccer academy at midseason.Participants:One hundred one academy soccer players (mean age 14.3 ± 1.8 years).Intervention:All players underwent clinical examinations to classify groin pain by the Doha agreement taxonom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In this regard, it is interesting to note that radiological signs of adductor longus tendinopathy are present in as many as 71% of asymptomatic subjects compared with 72% found in the population of symptomatic subjects [54]. It is obvious that we can raise some reasonable doubts about the fact that GPS is most frequently diagnosed as adductor tendinopathy [4,76,77]; indeed, in our recent study [40], we reported that adductor tendinopathy is responsible for only about 2% of cases of LSGPS. These data must undoubtedly cause us to reflect on how imprudent it is to stop at a simple diagnosis of this type without considering other possible pathological associations [24,40].…”
Section: Discussionmentioning
confidence: 82%
“…In this regard, it is interesting to note that radiological signs of adductor longus tendinopathy are present in as many as 71% of asymptomatic subjects compared with 72% found in the population of symptomatic subjects [54]. It is obvious that we can raise some reasonable doubts about the fact that GPS is most frequently diagnosed as adductor tendinopathy [4,76,77]; indeed, in our recent study [40], we reported that adductor tendinopathy is responsible for only about 2% of cases of LSGPS. These data must undoubtedly cause us to reflect on how imprudent it is to stop at a simple diagnosis of this type without considering other possible pathological associations [24,40].…”
Section: Discussionmentioning
confidence: 82%
“…The HAGOS follows the full COSMIN checklist [26] for the development and testing of a patient‐reported outcome measures (PROMs) instrument and it consists of six separate subscales assessing: (1) pain; (2) symptoms; (3) physical function in daily living (ADL); (4) physical function in sport and recreation (Sport/Rec); (5) participation in physical activities (PA) and (6) hip and/or groin‐related quality of life (QoL). It is a valid [5, 45], reliable [18], responsive [48] and recommended [6, 7, 48] PROMs questionnaire for groin pain. Each subscale is scored as a percentage of the total possible score, ranging from 0 to 100, where 0 indicates severe hip and/or groin‐related problems and 100 indicates no problems.…”
Section: Methodsmentioning
confidence: 99%